The Socio-Entrepreneurship Potential of Migrant Workers during the Covid-19 Era: A Mapping Study in Suralaga, East Lombok - Saipul Hamdi; Oryza Peneumatica Inderasari; Syarifuddin Syarifuddin; Indah Firgina Sari (Jurnal Kawistara, 2023)
The article aims to map the socio-entrepreneurship potential of migrant workers in the Covid-19 era. This mapping is vital to identify the potential that migrant workers have since they seek diversification during the pandemic years. In particular, this paper attempts to investigate the potential of this community as a socio-entrepreneurship resource for migrant workers as it has been seen essential an alternative approach to mitigating the effects of Covid-19. This study focuses on the Suralaga district, an area in East Lombok, which is known for a high number of migrant workers. This study is based on a qualitative approach and phenomenological methodology to gather and analyze data for six months (January–June 2022). There are 25 informants total in this study, 15 of whom are men and 10 of them are women. We used a variety of techniques to gather the data, including participant observation, in-depth interviews, focus groups, and documentation. The results of the study demonstrate that because of their low educational attainment—the majority of migrant employees having only completed elementary or junior high school—migrant workers have limited knowledge and skill, therefore it is difficult to find a job when they finished the contract and back home. In terms of natural potential, the Suralaga region's terrain is part of a farming area, where the majority of people work as farmers and grow tomatoes and chilies. The finding of this research also demonstrates the critical role that micro, small, and medium-sized businesses play in fostering the economic growth of migrant workers and serving as a counterweight to Covid-19's hegemonic middle class.